Epitaxial growth of (111)-oriented LaAlO3/LaNiO3 ultra-thin superlattices - Middey, S. (2014)
The epitaxial stabilization of a single layer or superlatticestructures composed of complex oxide materials on polar (111) surfaces is severely burdened by the reconstructions at the interface that commonly arise to neutralize the polarity. We report on the synthesis of high quality LaNiO3/mLaAlO3 pseudo cubic (111) superlattices on polar (111)-oriented LaAlO3, the proposed complex oxide candidate for a topological insulating behavior. Comprehensive X-Ray diffraction measurements, reflection high energy electron diffraction, and element specific resonant X-ray absorption spectroscopy affirm their high structural and chemical quality. The study offers an opportunity to fabricate interesting interface and topology controlled (111)-oriented superlattices based on ortho-nickelates.